The Commodification of Health Care in Kerala, South India: Science, Consumerism and Markets - Caroline Wilson (University of Sussex, 2010)
In India, alongside Information Technology, health care has become a leading sector in the country‘s development as a ̳knowledge economy‘ (World Bank 2005). One of the major achievements and beacons of economic reform is the growth of some of the most technologically advanced hospitals in the world. This thesis examines the social processes shaping the expansion of the private health care system in the state of Kerala, South India, where large corporate hospitals and ̳super-speciality‘ medicine have spread throughout urban and many rural areas. It explores the intersections between the local and the global, as the health system becomes the major driver of industrial development, unevenly linking the local health care system to the global marketplace for technologies, health care professionals and patients. It examines the three faces of the health care system in Kerala - as a knowledge industry and route to social mobility for the middle classes, in particular doctors and nurses; secondly, as a consumer economy, as people prioritise spending on health care and shop for treatment in the urban marketplace; and finally as a moral economy, as people develop high levels of dependency on doctors, hospitals and technologies in the hope of receiving good health care. The ethnography is set in Malabar, Northern Kerala, where the expansion of private health care has been financed by remittances from migration to the Arabian Gulf countries. The thesis examines the influence of migration and economic reforms on local ecologies of health and health care; the impact of the globalisation of trade in health services in the developing world; the relationship between the private health care system and the middle classes in South Asia; and the role of markets in the delivery of health services. Based on 18 months of participant observation across the urban and rural health care market with local communities of doctors and patients, it examines how doctors and patients adjust to a changing ecology and economy of health care.